Respiratory Function in Voluntary Participating Patagonia Sea Lions (Otaria flavescens) in Sternal Recumbency - Fahlman, Andreas; Madigan, Johnny (Frontiers in Physiology, 2016)
We measured esophageal pressures (n=4), respiratory flow rates (n=5), and expired O2 and CO2 (n=4) in five adult Patagonia sea lions (Otaria flavescens, body mass range 94.3-286.0 kg) during voluntary breaths while laying down. The data were used to estimate the dynamic specific lung compliance (sCL, cmH2O-1), the O2 consumption rate (VO2) and CO2 production rates (VCO2) during rest. Our results indicate that the resting tidal volume in Patagonia sea lions is approximately 47-73% of the estimated total lung capacity. The esophageal pressures indicated that expiration is passive during voluntary breaths. The average sCL of dolphins was 0.41±0.11 cmH2O−1, which is similar to those measured in anesthetized sea lions and awake cetaceans, and significantly higher as compared with humans (0.08 cmH2O−1). The average estimated and using breath-by-breath respirometry were 1.023 ± 0.327 L O2 min-1 (range: 0.695-1.514 L O2 min−1) and 0.777 ± 0.318 L CO2 min-1, (range: 0.510-1.235 L CO2 min-1), respectively, which is similar to previously published metabolic measurements from California and Steller sea lions using conventional flow-through respirometry. Our data provide end-tidal gas composition and provide novel data for respiratory physiology in pinnpeds, which may be important for clinical medicine and conservation efforts.